A modified chi-square test for Bertholon model with censored data. Issue 1 (2nd January 2017) - Chouia, Sana; Seddik-Ameur, Nacira
ABSTRACT: In this work, we propose the construction of a chi-squared goodness-of-fit test in censored data case, for Bertholon model which can analyse various competing risks of failure or death. This test is based on a modification of the Nikulin-Rao-Robson (NRR) statistic proposed by Bagdonavicius and Nikulin (2011a, 2011b ) for censored data. We applied this test to numerical examples from simulated samples and real data.